The Relationship between Readiness and Facilitation of Self-Directed Learning and Academic Achievement: A Comparative Study of Web-Based Distance Learning Models of Two Universities - Haron, Shireen (2003)
The purpose of this research was to explore the practise of self-directed learning in web-based learning environments. The main objectives of the research were: (1) to determine whether students following UNITAR and UiTM web-based learning models were ready as self-directed learners, (2) to determine whether the web-based learning models facilitate self-directed learning, (3) to establish the relationship between level of readiness and academic achievement and between level of facilitation of self-directed learning and academic achievement. The research employed the quantitative methodology. Data were collected using two survey instruments. The Self-Directed Learning Readiness Scale or SDLRS is developed and designed to measure the level of readiness for self-directed learning among adult learners. The second instrument is the Self-Directed Learning in Webbased Learning Environment Survey Instrument or the SDLWEB which was designed to measure to the level of facilitation of self directed learning in web-based learning models. Approximately 244 students from two universities participated in this research. There were two data sets involved in this research. The first data set comprised of 109 students responding to the SDLRS instrument. From the 109 students, 53 students were from UNITAR and 56 students were from UiTM. The second data set consist of 135 students responding to the SDLWEB instrument. From the 135 students, 65 students were from UNITAR and 70 students were from UiTM. The research revealed that Malaysian web-based learners are below average in their level of readiness for self-directed learning. Both groups from UiTM and UN ITAR have a mean score of 203 and 189 respectively. However, UiTM’s web-based distance learners have a higher SDLRS score than UNITAR’s web-based distance learners. Test of significance shows that there is a significant different between the means of the two groups. The research also revealed that Malaysian web-based learning models are average in their capability to facilitate self-directed learning. Results shows that UNITAR have a higher SDLWEB score than UiTM that is 124 for UNITAR and 118 for UiTM. The t-test shows that there is no significant difference between the two groups means in the level of facilitation. The research also revealed that there is a strong and positive relationship between level of readiness and academic achievement. The test of significance shows that the relationship is significant. However, there is a weak yet positive relationship between the level of facilitation of self-directed learning and academic achievement. The test of significance shows that the relationship is insignificant. The research concluded that (1) there is a need to provide students’ with knowledge, skills, and support to be more ready for self-directed learning. (2) there is a need for universities that offer web-based distance education programs to developed the webbased learning models to be able to highly facilitate self-directed learning. Further research should explore these areas within different web-based distance learning models.